MicroRNA172b-5p/trehalose-6-phosphate synthase module stimulates trehalose synthesis and microRNA172b-3p/AP2-like module accelerates flowering in barley upon drought stress - Swida-Barteczka, Aleksandra; Pacak, Andrzej; Kruszka, Katarzyna; Nuc, Przemyslaw; Karlowski, Wojciech M.; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2023)
MicroRNAs are major regulators of gene expression during plant development under normal and stress conditions. In this study we analysed expression of 149 conserved miRNAs during drought stress applied to barley ready to flower. The dynamics of miRNAs expression was observed also after re-watering. Target mRNAs were experimentally identified for all but two analysed miRNAs and 41 of the targets were not reported before. Drought stress applied to barley induced accelerated flowering coordinated by a pair of two differently expressed miRNAs originating from a single precursor: hvu-miR172b-3p and hvu-miR172b-5p. Increased expression of miRNA172b-3p during drought lead to downregulation of four AP2-like genes by their mRNA cleavage. In parallel, the downregulation of miRNA172b-5p level results in increased level of a newly identified target, trehalose-6-phosphate synthase, key enzyme in trehalose biosynthesis pathway. Therefore, drought treated plants have higher trehalose content, a known osmoprotectant, which level is rapidly dropping after watering. Also, trehalose-6-phosphate, an intermediate of trehalose synthesis pathway, is known to induce flowering. The hvu-miRNA172b-5p/trehalose-6-phosphate synthase and hvu-miRNA172b-3p/AP2-like create a module leading to osmoprotection and accelerated flowering induction during drought.